Best of retirement planning - Haynes, Marion E. ed. (Crisp Pub. Menlo ParkUS, 1995)
Presents a compilation of articles on retirement and deals with issues such as: developing a retirement programme; classes for pre-retirees; readiness for retirement; financial considerations e.g. insurance; hazards of being a mature consumer; selecting a money manager; lifestyle issues e.g. re-location after retirement; and, retired couples.